2018
DOI: 10.1007/s13744-018-0625-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Distance Among Colonies and Resource Availability Explain the Intercolonial Aggressiveness in Nasutitermes aff. coxipoensis?

Abstract: Aggressive behaviour can ensure animal access to local resources. To reduce constant costs in the defence of territories, species could save energy with conflicts avoiding aggression with neighbour or in situations with abundance of resources. In the present study, we analysed the effect of distance among colonies and resource availability on the aggression level and responses to chemical cues of Nasutitermes aff. coxipoensis (Holmgren) (Termitidae: Nasutitermitinae). Manipulation of resource offer was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Behaviors preventing conflict escalation are widespread across taxa (e.g., Akino, Knapp, Thomas, & Elmes, 1999;Aureli, Cords, & van Schaik, 2002;Baan, Bergmüller, Smith, & Molnar, 2014;Gobush & Wasser, 2009;Lhomme, Ayasse, Valterová, Lecocq, & Rasmont, 2012;Nehring, Dani, Turillazzi, Boomsma, & d'Ettorre, 2015;Pierce et al, 2002;Thierry et al, 2008). In termites specifically, aggressiveness depends on a range of ecological factors such as diet (Florane, Bland, Husseneder, & Raina, 2004), caste ratios (Roisin, Everaerts, Pasteels, & Bonnard, 1990), nestmate recognition (Delphia, Copren, & Haverty, 2003;Haverty & Thorne, 1989), group composition (Haverty & Thorne, 1989), territoriality (Adams & Levings, 1987;Ferreira et al, 2018;Levings & Adams, 1984), and resource availability (Cristaldo, Araújo, et al, 2016). In addition, aggression between termite colonies of the same species, which would be presumably less predictable due to a higher relatedness, may be inconsistent (Binder, 1987).…”
Section: Mechanisms Of Conflict Avoidancementioning
confidence: 99%
“…Behaviors preventing conflict escalation are widespread across taxa (e.g., Akino, Knapp, Thomas, & Elmes, 1999;Aureli, Cords, & van Schaik, 2002;Baan, Bergmüller, Smith, & Molnar, 2014;Gobush & Wasser, 2009;Lhomme, Ayasse, Valterová, Lecocq, & Rasmont, 2012;Nehring, Dani, Turillazzi, Boomsma, & d'Ettorre, 2015;Pierce et al, 2002;Thierry et al, 2008). In termites specifically, aggressiveness depends on a range of ecological factors such as diet (Florane, Bland, Husseneder, & Raina, 2004), caste ratios (Roisin, Everaerts, Pasteels, & Bonnard, 1990), nestmate recognition (Delphia, Copren, & Haverty, 2003;Haverty & Thorne, 1989), group composition (Haverty & Thorne, 1989), territoriality (Adams & Levings, 1987;Ferreira et al, 2018;Levings & Adams, 1984), and resource availability (Cristaldo, Araújo, et al, 2016). In addition, aggression between termite colonies of the same species, which would be presumably less predictable due to a higher relatedness, may be inconsistent (Binder, 1987).…”
Section: Mechanisms Of Conflict Avoidancementioning
confidence: 99%
“…aff. coxipoensis perform more fighting among individuals from neighboring colonies compared to those from distant one, especially when the local supply of resources is reduced (Ferreira et al, ). These results, together, allow us to infer that in natural conditions of food scarcity (e.g., where neighboring colonies are more likely to consume similar resources), individuals of N .…”
Section: Discussionmentioning
confidence: 99%
“…In termites, it is common to observe the simultaneous use of same food source by several species (Roisin et al, 2006;Schuurman, 2006) or even the nest-sharing among different termite species (e.g., inquiline; Costa, De, Lima-Filho, & Brandão, 2009;Cristaldo, Rosa, Florencio, Marins, & DeSouza, 2012). On the other hand, termite species also exhibit defense of their territories (Adams & Levings, 1987;Levings & Adams, 1984) and a greater number of conflicts with neighboring colonies than distant ones (Dunn & Messier, 1999;Ferreira et al, 2018). In addition, some studies have been shown that colony fusion of neighboring colonies, with reduction of agonistic behaviors, is an adaptive strategy based in the cost/benefit balance of local conditions (e.g., food resource offer; Deheer & Vargo, 2004;Korb & Roux, 2012;Matsuura & Nishida, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations